(untitled) (LACCEI, 2024)
At present, a fundamental factor for the success of the projects is the satisfaction of the needs and expectations of the interested parties, since they are the ones who provide the resources, present the needs for the realization of the projects, and accept or not the result. thereof. With the realization of these projects, the sustainability of the companies and the development of the communities are allowed. This research has the purpose of designing a good practice guide for the management of stakeholders of the improvement projects carried out by Megainversiones S.A. Its design was based on different project management standards, mainly P.M. I. (2017), and on the provenance theories, methodologies and models of Orpwood (1985) and Trentim (2015), power – influence / interest matrix of Gardner (1986), level of participation of P.M.I. (2017) and prominence exposed by Mitchell, Agle and Wood (1997), in such a way that they can successfully conclude their projects. It is an exploratory research with a mixed approach. It was carried out in 4 stages The data collection was done through the systematic review of the existing scientific literature. A survey was applied to a sample of 141 interested parties out of the 326 that make up Megainversiones S.A. simple random sampling was used. What allowed to make a diagnosis of the interested parties, with this information an action plan is proposed After identifying weaknesses and formulating improvement strategies, the good practice guide is designed, and in stage 4 the proposed guide for stakeholder management is materialized.